Perbandingan Metode Latihan Dan Motivasi Latihan Terhadap Kemampuan Footwork Atlet Tenis Meja - Suhermon Suhermon; Arisman Arisman; Siska Siska; Tofikin Tofikin; Ferry Hendriyanto (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2023)
The problem in this study was the low footwork ability of PTM Pasir Pengaraian table tennis athletes. This type of research is quasi-experimental using ANOVA 2 x 2 design. The population of this study is 20 people. Sampling used the total sampling technique then carried out a training motivation test with a motivational questionnaire, after the motivational questionnaire data was obtained, it was divided into 5 people per group using the Matching technique so that a sample of 20 athletes was obtained. After the sample was obtained, it was given treatment in 20 meetings. The results of data analysis in this study are 1). There is a significant difference in the footwork ability of PTM Pasir Pengaraian table tennis athletes who are given shadow play training and athletes who are given ladder drill training significantly with a significance value of 0.048. 2). There is a significant difference in the footwork ability of PTM Pasir Pengaraian table tennis athletes who have high exercise motivation and athletes who have low exercise motivation significantly with a significance value of 0.000. 3). There was no interaction between training variants and exercise motivation on improving the footwork ability of PTM Pasir Pengaraian table tennis athletes with a significance value of 0.759. 4). the footwork ability of PTM Pasir Pengaraian table tennis athletes who were given ladder drill training was better than shadow play in the group of athletes who had high training motivation but not significant with a significance value of 0.268. 5). The footwork ability of PTM Pasir Pengaraian table tennis athletes who were given ladder drill training was better than shadow play in the group of athletes who had low training motivation but not significant with a significance value of 0.113.